ADHAD and intelligence in a clinical sample: comparison of the intellectual profile of the WISC-IV between subjects with ADHD and Learning Disorder - Álava Sordo, Silvia; Cantero-García, María; Garrido-Hernansaiz, Helena; Sánchez-Iglesias, Iván; Santacreu Más, José; González-Moreno, Jesús (Pulso. Revista de educación, 2021)
Attention deficit/hyperactivity disorder (ADHD) is characterized by a persistent pattern of inattention and/or hyperactivity/impulsivity that negatively interferes with the development and the normal social, academic, and occupational functioning of those who suffer from it. The reviewed literature shows that there are no significant differences in the Total Intelligence Quotient between individuals with ADHD and the population with typical development, but performance in the Work Memory and Processing Speed tests is lower. The objective of this study is to find out if there are differences in the intellectual profile, measured with the WISC-IV, in a clinical sample of 234 children with ADHD and 230 children with Learning Disorder (AT), with the aim of improving the differential diagnosis ability. The results showed that neither children with ADHD nor those with AT scored lower than expected on intelligence.